B cell depletion in the treatment of multiple sclerosis. (4th March 2019) - Myhr, Kjell-Morten; Torkildsen, Øivind; Lossius, Andreas; Bø, Lars; Holmøy, Trygve
ABSTRACT: Introduction : Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system. The latest development of B-cell depletion by anti-CD20 monoclonal antibodies has been a large step forward in the treatment of this devastating disease. Areas covered : In this manuscript, we review mechanisms of action, efficacy, safety, and tolerance of anti-CD20 therapies for MS, including rituximab, ocrelizumab, and ofatumumab. Expert opinion : B-cell depletion efficiently suppresses acute inflammatory disease activity in relapsing-remitting MS (RRMS), and may slowdown progression in primary progressive MS (PPMS). The treatment is generally well tolerated, with manageable adverse events related to infusion reactions and infections. Ocrelizumab, a humanized anti-CD20 monoclonal antibody, is the first therapy to be approved for the treatment of both RRMS and PPMS.